Continuous and large-scale synthesis of Ni–Co PBA nanoparticles with a tunable particle size in a microreactor. (2nd December 2022) - Wang, Huanhuan; Qu, Qi; Liu, Zhiming; He, Yan; Gao, Jiangshan
Abstract : A micro-mix strategy for the continuous and large-scale synthesis of Ni–Co PBA nanoparticles. Abstract : Herein, we report a micro-mix strategy for the continuous and large-scale synthesis of Ni–Co PBA nanoparticles. The technique presented in this study allows the particle size to be controlled in the 165 nm to 350 nm range while maintaining a high specific surface area (250 m 2 g −1 ) and cubic structure. Furthermore, the particles exhibit superior dispersity and have a more homogeneous particle size than those prepared using the conventional stirring-mix method due to the drastic collisions that occur in the microchannel during the precipitation process. The present study demonstrates that the concentration of raw materials and feed flow rates in the microreactor effectively control the particle size during mixing. The high concentration of raw materials could decrease the particle size, and the particle size is decreased with the increasing feed flow rates when Re (Reynolds number) <783. Particularly, when 783 < Re < 1567, the particle size remains stable (about 165 ± 10 nm). Additionally, the space-time yield (STY) of Ni–Co PBA is 471 kg m −3 d −1 . Finally, the continuous flow microreactor can continuously fabricate large-scale and high-quality Ni–Co PBA crystals with distinct morphological features in a short period of time, providing an effective alternative to the time-consuming and multi-step MOF synthesis method.